Pelaksanaan Tugas Camat dalam Membina dan Mengawasi Kegiatan Pembangunan Desa di Kecamatan Sulamu Kabupaten Kupang - Melton Herison Nenometa; Hernimus Ratu Udju; Cyrilius W,T. Lamataro (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The implementation of the Subdistrict Head's duties in fostering and overseeing village development activities in Sulamu Subdistrict, Kupang Regency, can be categorized as uneven and not well-realized. The village development programs in Sulamu Subdistrict can be said to have not been well-implemented, as evidenced by several issues, including insufficient progress in physical infrastructure such as roads and bridges being in poor condition. The aim of this research is to identify the factors hindering the execution of the Subdistrict Head's duties. This study is based on empirical juridical research, employing an approach that utilizes primary data collected directly from the research site. Based on the findings, the inhibiting factors of the Subdistrict Head's duties include human resources factors, infrastructure factors, and coordination factors.